Cover Feature: Super‐resolution Imaging of Amyloid Structures over Extended Times by Using Transient Binding of Single Thioflavin T Molecules (ChemBioChem 18/2018). (11th September 2018) - Spehar, Kevin; Ding, Tianben; Sun, Yuanzi; Kedia, Niraja; Lu, Jin; Nahass, George R.; Lew, Matthew D.; Bieschke, Jan
Abstract : The cover feature picture shows an amyloid fibril being imaged by using transient amyloid binding super‐resolution microscopy. As thioflavin T molecules spontaneously bind to amyloid structures, they emit flashes of fluorescence, and these blinking events can be used to visualize native amyloid fibrils at nanoscale resolution for several days. More information can be found in the communication by M. D. Lew, J. Bieschke et al. onpage 1944 in Issue 18, 2018 (DOI:10.1002/cbic.201800352 ).